2008
DOI: 10.1007/s10470-008-9240-3
|View full text |Cite
|
Sign up to set email alerts
|

Digital based calibration technique for continuous-time bandpass sigma-delta analog-to-digital converters

Abstract: In this paper, a calibration technique for Noise Transfer Function (NTF) optimization of Continuous-Time Bandpass Sigma Delta (CT BP RD) modulators is presented. The proposed technique employs a test tone applied at the input of the quantizer to evaluate the noise transfer function of the Analog-to-Digital Converter (ADC) using the capabilities of the Digital Signal Processing (DSP) platform usually available in mixed-mode systems. Once the ADC output bit stream is captured, necessary information to generate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Trimming is needed to correct or compensate the drift in circuit components to obtain the optimum performance from the modulator. There are some publications that discuss calibration of CT Σ∆ modulators, but they are limited to calibration of the modulator notch frequency [4]- [6]. In this paper, it is shown that there are more parameters to calibrate other than the notch frequency.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Trimming is needed to correct or compensate the drift in circuit components to obtain the optimum performance from the modulator. There are some publications that discuss calibration of CT Σ∆ modulators, but they are limited to calibration of the modulator notch frequency [4]- [6]. In this paper, it is shown that there are more parameters to calibrate other than the notch frequency.…”
Section: Introductionmentioning
confidence: 98%
“…One of the main issues in BP CT Σ∆ modulators is the poor accuracy and sensitivity to process variations [4]. Trimming is needed to correct or compensate the drift in circuit components to obtain the optimum performance from the modulator.…”
Section: Introductionmentioning
confidence: 99%